In vitro, in silico and in vivo studies of the structure and conformational dynamics of DNA Polymerase I - Sustarsic, M (2015)
DNA polymerases are a family of molecular machines involved in high-fidelity DNA replication and repair, of which DNA polymerase I (Pol) is one the best-characterized members. Pol is a strand-displacing polymerase responsible for Okazaki fragment synthesis and base-excision repair in bacteria; it consists of three protein domains, which harbour its 5’-3' polymerase, 3’-5’ exonuclease and 5’ endonuclease activities. In the first part of the thesis, we use a combination of single-molecule Förster resonance energy transfer (smFRET) and rigid-body docking to probe the structure of Pol bound to its gapped-DNA substrate. We show that the DNA substrate is highly bent in the complex, and that the downstream portion of the DNA is partly unwound. Using all-atom molecular dynamics (MD) simulations, we identify residues in the polymerase important for strand displacement and for downstream DNA binding. Moreover, we use coarse-grained simulations to investigate the dynamics of the gapped-DNA substrate alone, allowing us to propose a model for specific recognition and binding of gapped DNA by Pol. In the second part of the thesis, we focus on the catalytically important conformational change in Pol that involves the closing of the ‘fingers’ subdomain of the protein around an incoming nucleotide. We make use of the energy decomposition method (EDM) to predict the stability-determining residues for the closed and open conformations of Pol, and test their relevance by site-directed mutagenesis. We apply the unnatural amino acid approach and a single-molecule FRET assay of Pol fingers-closing, to show that substitutions in the stability-determining residues significantly affect the conformational equilibrium of Pol. In the final part of the thesis, we attempt to study Pol in its native environment of the living cell. We make use of the recently developed method of internalization by electroporation, and optimize it for organically labelled proteins. We demonstrate the internalization and single-molecule tracking of Pol, and provide preliminary data of intra-molecular FRET in Pol, both at the single-cell and single-molecule levels. Finally, by measuring smFRET within an internalized gapped-DNA construct, we observe DNA binding and bending by endogenous Pol, confirming the physiological relevance of our in vitro Pol-DNA structure.